Pretreatment metabolic tumor volume as a prognostic factor in HPV‐associated oropharyngeal cancer in the context of AJCC 8th edition staging. Issue 10 (26th July 2018) - Floberg, John M.; DeWees, Todd A.; Chin, Re‐I; Garsa, Adam A.; Dehdashti, Farrokh; Nussenbaum, Brian; Oppelt, Peter J.; Adkins, Douglas R.; Gay, Hiram A.; Thorstad, Wade L.
Abstract: Background: This study evaluates the prognostic significance of 18 F‐fluorodeoxyglucose‐positron emission tomography ([F‐18]FDG‐PET)‐derived metabolic tumor volume (MTV) in human papillomavirus (HPV)‐associated oropharyngeal squamous cell carcinomas (OPSCCs) in the context of AJCC 8th edition staging. Methods: We performed a retrospective study of HPV‐associated OPSCCs treated with postoperative or definitive radiation. The prognostic significance of pretreatment MTV for freedom from recurrence (FFR), freedom from distant metastasis (FFDM), and overall survival (OS) was determined using Kaplan‐Meier analysis. Multivariate analysis (MVA) was performed using Cox regression. Results: In this 153‐patient cohort, stratifying by the optimum MTV (24 cm 3 ) was prognostic for FFR ( P = .0002), FFDM ( P = .001), and OS ( P < .0001). Metabolic tumor volume (MTV) was prognostic of FFR in AJCC 8th edition stage I/II ( P = .03), and stage III patients ( P = .04). On multivariate analysis only MTV was a significant factor for OS. Conclusion: Metabolic tumor volume (MTV) is a significant prognostic factor in HPV‐associated OPSCCs, independent of AJCC 8th edition stage.